New Domestic Communities. For a Semiotic Analysis of the Movie The Spanish Apartment - Franco , Maria Giulia (E|C, 2024)
My proposal is to semiotically analyze the logics regarding the formation of a collective actor, a living community, formed starting from the sharing of the same action programme, the adhesion to a new experience of coexistence in a new house. The space and its re-semantization will in fact be the main recipient in establishing a renewed form of life, in which each individuality will recognize itself relationally. I will address this question through the semiotic study of a film: L’appartamento spagnolo. One story of coexistence that act as effective text in bringing out the process of establishing a community; investigating the redefinition of meanings regarding the semantic categories of public/private, individual/collective or even intimate/foreign. I will thus explore the role of new policy of cohabitation, prerequisite for a form of living together. The final result will lead to the creation of a new collective, in a new dimension in which space and subjects define each other mutually.